A redox- and proton-coupled inner membrane transporter mediates copper import to the bacterial cytoplasm - Caitlin D. Palmer; Madujika A. Horadigala Gamage; Madeline B. Ho; Nadeesha T. Liyana Withanage; Rose C. Hadley; Brian M. Hoffman; Gabriele Meloni; Amy C. Rosenzweig (Proceedings of the National Academy of Sciences, 2026)
Copper homeostasis in bacteria requires tightly regulated import systems to balance copper’s essential redox functions with its inherent cytotoxicity; yet, the mechanisms of cytoplasmic copper uptake remain poorly understood. In particular, the widespread CopD family of transmembrane proteins has been linked genetically to cytoplasmic copper import, but has not been mechanistically characterized. Here, using in vivo uptake assays, proteoliposome-based, real-time copper translocation kinetic measurements, and spectroscopic and electrochemical analyses, we demonstrate that CopD from the methanotroph Methylosinus trichosporium OB3b functions as a Cu + /H + symporter and a Cu 2+ reductase. Real-time transport measurements reveal transporter-mediated saturable transport with micromolar Cu + affinity and rapid translocation rates consistent with facilitated diffusion or potential secondary active transport, and pH-sensitive fluorescence assays establish obligatory proton cotransport coupled to Cu + translocation. Three conserved residues, two histidines and a tryptophan, predicted to reside in the periplasmic and transmembrane regions, respectively, were identified as critical determinants of copper uptake, with likely roles in substrate coordination and gating. Notably, CopD contains a C-terminal periplasmic cytochrome c domain with a complex electron paramagnetic resonance spectrum dominated by a low-spin, six-coordinate heme with a midpoint potential of 138 ± 5 mV. Spectroscopic and electrochemical data show that this heme can reduce Cu 2+ to Cu + , both in solution and when copper is bound to the cognate M. trichosporium OB3b periplasmic chaperone CopC. These findings support a model in which CopD couples periplasmic Cu 2+ reduction to Cu + /H + symport across the inner membrane, establishing a new paradigm for bacterial copper import and metal transporter function.